Crises and unpredictability in developing countries. - San-Martín-Albizuri, Nerea; Rodriguez-Castellanos, Arturo (Third World Quarterly, 2018)
Developing countries have suffered most of the financial crises in the context of the process of economic and financial globalisation. Both current and previous crises have revealed that unpredictability is a feature common to all the episodes which occurred during the process of globalisation. Although certain alarms went off, any of those external financial crises were actually predicted by the advanced methods in use for prediction and country risk analysis. Taking into consideration the information above, the aim of this paper is to check the ability to foresee external financial crises in developing countries of both the country risk index published by Euromoney and the Credit Ratings variable included therein. We have focused on the external financial crises that took place between 1992 and 2011, that is, in a full globalisation era. The results are negative. It appears that neither the index nor the sovereign ratings are able to reflect early enough the vulnerabilities that arise previously to the setting off the crisis episodes. This leads us to conclude that the existing models of country risk have limits. Thus, it would necessary to develop new instruments to measure this risk, considering uncertainty as an essential feature of the current economic and financial environment.